1999
DOI: 10.1097/00042560-199904150-00014
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Risk-Taking Consequences of Drug Use Among HIV-Infected Women

Abstract: Drug users in this cohort were more likely to engage in behaviors that place them at risk for STDs, to have elevated STD prevalence, and to have lower perceived health across several indices. Identification of drug use and treatment for it need to be a central component of HIV care for women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Now, difficulty in establishing care can be added to that list. Previous research has also associated substance use with greater risk of unprotected sexual encounters (Eich-Hochli et al, 1998;Hays et al, 1997;Novotna et al, 1999). Clearly, efforts to identify and treat substance users should begin as soon as clients enter a care system.…”
Section: Discussionmentioning
confidence: 99%
“…Now, difficulty in establishing care can be added to that list. Previous research has also associated substance use with greater risk of unprotected sexual encounters (Eich-Hochli et al, 1998;Hays et al, 1997;Novotna et al, 1999). Clearly, efforts to identify and treat substance users should begin as soon as clients enter a care system.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that those in the WIHS cohort at highest risk for HCV acquisition had already acquired infection before enrollment. Additionally, once enrolled in the study, the WIHS participants were likely to receive standard counseling regarding safe sex practices and risk of ongoing drug use, although the impact of such messages is unclear [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Factors previously shown to be associated with non-adherence include heterosexual orientation and non-Latino ethnicity (Power et al, 2003), older age (Mellins, Kang, Leu, Havens, & Chesney, 2003), increased viral load (Paterson et al, 2000), lower levels of social support (Power et al, 2003), alcohol and drug use (Chesney et al, 2000;Mellins et al, 2003), and depression (Murphy et al, 2001;Paterson et al, 2000). Factors previously shown to be associated with unprotected sex among HIV-positive individuals include alcohol and recreational drug use (Kalichman, 1999;Lee, Galanter, Dermatis, & McDowell, 2003;Novotna et al, 1999), number of sexual partners (Lightfoot, Song, Rotheram-Borus, & Newman, 2005;Wyatt et al, 2002), self-identified homosexual orientation (Denning & Campsmith, 2005), female gender (in studies comparing heterosexual women and men) (Latkin, Forman-Hoffman, D'Souza, & Knowlton, 2004;Tucker, Burnam, Sherbourne, Kung, Gifford, 2003b), education (less than high school among MSM) (Denning & Campsmith, 2005), less social support (Reilly & Woo, 2004;Sherman & Kirton, 1999), viral load (Vanable, Ostrow, & McKirnan, 2003), health status (Sherman & Kirton, 1999), depressive symptoms and lower anxiety among MSM (Parsons, Halkitis, Wolitski, Gomez, & Seropositive Urban Men's Study Team, 2003). The variables examined in this study were sexual orientation, IDU, recreational drug use, number of male and female partners, number of AIDS-related symptoms, viral load, Anger-Burnout, BDI, STAI, perceived stress, social support, self-efficacy for adherence, and attitudes about ART.…”
Section: Data Analysesmentioning
confidence: 99%